Limonin: Advances in extraction, synthesis, pharmacological mechanisms, and structural optimization for therapeutic potential. - Meng, Xianghui; Xi, Zhichao; Chen, Xinwei; Green, Donovan; Zhou, Yunhao; Xian, Yao; Zhang, Hongmei (Fitoterapia, 2025)
Limonin, a highly oxygenated nor-triterpenoid phytochemical abundant in Citrus plants, has attracted considerable attention because of its diverse pharmacological properties. Its significant anti-inflammatory, antioxidant, anticancer, antifungal, and antiviral activities have been demonstrated in recent studies and are associated with the modulation of multiple signaling pathways, highlighting its potential as a valuable lead compound for therapeutic development. However, poor solubility and limited bioavailability constrain its practical application, prompting interest in chemical synthesis and structural modification strategies to enhance therapeutic potential. This review systematically summarizes recent advances in the extraction, synthesis, pharmacological mechanisms, and structural optimization of limonin, including comparisons of extraction processes and analyses of structure–activity relationships. It further aims to encourage additional research on limonin and its derivatives and to support their clinical translation. [Display omitted] • Advances in extraction, synthesis, pharmacology, and structural modification of limonin are systematically reviewed. • Emerging extraction and synthetic strategies enhance the recovery and sustainability of limonin. • Limonin exhibits anti-inflammatory, antioxidant, and anticancer effects through multi-target mechanisms. • Structural modifications produce derivatives with improved pharmacological activity and bioavailability.